Contribution of MINCLE-SYK Signaling to Activation of Primary Human APCs by Mycobacterial Cord Factor and the Novel Adjuvant TDB - Ostrop, Jenny; Jozefowski, Katrin; Zimmermann, Stephanie; Hofmann, Katharina; Strasser, Erwin; Lepenies, Bernd; Lang, Roland (Journal of Immunology, 2015)
Trehalose-6,6-dimycolate (TDM), the mycobacterial cord factor, is an abundant cell wall glycolipid and major virulence factor of Mycobacterium tuberculosis. Its synthetic analog trehalose-6,6-dibehenate (TDB) is a new adjuvant currently in phase I clinical trials. In rodents, the C-type lectin receptors Mincle and Mcl bind TDB/TDM and activate macrophages and dendritic cells (DC) through the Syk-Card9 pathway. However, it is unknown whether these glycolipids activate human innate immune cells through the same mechanism. We performed in vitro analysis of TDB/TDM-stimulated primary human monocytes, macrophages, and DC; determined C-type lectin receptor expression; and tested the contribution of SYK, MINCLE, and MCL by small interfering RNA knockdown and genetic complementation. We observed a robust chemokine and cytokine release in response to TDB or TDM. MCSF-driven macrophages secreted higher levels of IL-8, IL-6, CCL3, CCL4, and CCL2 after stimulation with TDM, whereas DC responded more strongly to TDB and GM-CSF-driven macrophages were equally responsive to TDB and TDM. SYK kinase and the adaptor protein CARD9 were essential for glycolipid-induced IL-8 production. mRNA expression of MINCLE and MCL was high in monocytes and macrophages, with MINCLE and MCL proteins localized intracellularly under resting conditions. Small interfering RNA-mediated MINCLE or MCL knockdown caused on average reduced TDB- or TDM-induced IL-8 production. Conversely, retroviral expression in murine Mincle-deficient DC revealed that human MINCLE, but not MCL, was sufficient to confer responsiveness to TDB/TDM. Our study demonstrates that SYK-CARD9 signaling plays a key role in TDB/TDM-induced activation of innate immune cells in man as in mouse, likely by engagement of MINCLE.
EVALuna2:7676